THE EFFECT OF ADDING THE AMOUNT OF DIFFERENT DADIH ON THE ORGANOLEPTIC QUALITY OF TILAPIA (Oreochromis niloticus) BEKASAM - Cindi Harta Yuliana; N Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT                  Bekasam is a fermented fish product that has a salty and sour taste. Bekasam which is processed spontaneously is made by adding salt and carbohydrates (white rice). Dadih can be added to increase the number of lactic acid bacteria in the bekasam. The purpose of this research was to determine the effect of increasing the amount of different dadih in tilapia fish bekasam on the organoleptic quality. The method used in this research is exploratory and the results were analyzed descriptively. The treatments included D0 (without addition of dadih), D5 (addition of 5% dadih), D10 (addition of 10% dadih) and D15 (15% addition of dadih). The addition of dadih in sequence gives an odor value of 5.9; 7.9; 7.5; 7.2; taste 5.2; 8.0; 7.5; 6.9; texture 5.9; 7.4; 7.6; 7.7 and appearance 4.8; 7.7; 7.4; 6.5. The panelists liked the tilapia fish bekasam with 5% dadih addition, which was indicated by the characteristic fragrant odor, sour and alcoholic odor typical of the bekasam, the specific taste of the bekasam, salty and sour, chewy, soft texture, soft flesh and attractive appearance, slightly bright yellowish color. Keyword: Bekasam, Dadih, Organoleptic, Tilapia